SOSIALISASI PENGEMBANGAN TANAMAN TEMBAKAU DAN PENERAPAN TEKNIS BUDIDAYA TEMBAKAU UNTUK PENINGKATAN PRODUKTIVITAS PETANI DI SUMALU LEMBANG RANTEBUA - Kannapadang, Sepsriyanti; Oktafianus, Sion; Karuru, Sakti Swarno; Kannapadang, Dwibin (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
This community service program aims to improve farmers' knowledge and skills regarding the development of tobacco plants and the application of proper cultivation techniques to increase productivity in Lembang Rantebua, Rantebua District, North Toraja Regency. The activities were carried out on July 15, 2025 through counseling and direct training to farmer groups. The method used includes lectures, discussions, technical assistance, and demonstration plots focusing on land preparation and seed selection, fertilization management, environmentally friendly pest and disease control, and harvesting/post-harvest curing processes. The result of this activity showed that farmers gained improved understanding and skills in good tobacco cultivation practices, were able to adopt recommended cultivation techniques, and had better awareness of the importance of efficient input use for productivity enhancement. This program is expected to support tobacco agribusiness expansion and sustainably improve farmer income.